2010
DOI: 10.1186/1756-0500-3-149
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphic registration of motor activity reveals a more structured behavioural pattern in schizophrenia than in major depression

Abstract: BackgroundDisturbances in motor activity pattern are seen in both schizophrenia and depression. However, this activity has rarely been studied objectively. The purpose of the present study has been to study the complexity of motor activity patterns in these patients by using actigraphy.FindingsMotor activity was recorded using wrist-worn actigraphs for periods of 2 weeks in patients with schizophrenia and major depression and compare them to healthy controls. Average motor activity was recorded and three non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 26 publications
8
105
3
3
Order By: Relevance
“…Following data extraction 8 papers were excluded: 3 for having no interpretable data (Iverson, 2004;Ueda et al, 2005;Wolff, III et al, 1985), two conference abstracts with insufficient data (Deoras et al, 2010;Kelly et al, 2009), two for inappropriate comparisons (Lemke et al, 1998;Mendlowicz et al, 1999) and one as an exploratory study of non-linear dynamic measures of variability (Hauge et al, 2011). This left 19 papers from 16 studies suitable for detailed comparison Baune et al 2007;Berle et al, 2010;Coffield and Tryon, 2004;Faurholt-Jepsen et al, 2012;Foster et al, 1978;Glod et al 1992;Godfrey and Knight, 1984;Haynes et al, 2006;Joffe et al, 2009;Korszun et al, 2002;Raoux, 1994;Royant-Parola et al, 1986;Teicher et al, 1997;Todder et al, 2006;Todder et al, 2007;Volkers et al, 2002;Volkers et al, 2003;Winkler et al, …”
Section: Search Resultsmentioning
confidence: 99%
“…Following data extraction 8 papers were excluded: 3 for having no interpretable data (Iverson, 2004;Ueda et al, 2005;Wolff, III et al, 1985), two conference abstracts with insufficient data (Deoras et al, 2010;Kelly et al, 2009), two for inappropriate comparisons (Lemke et al, 1998;Mendlowicz et al, 1999) and one as an exploratory study of non-linear dynamic measures of variability (Hauge et al, 2011). This left 19 papers from 16 studies suitable for detailed comparison Baune et al 2007;Berle et al, 2010;Coffield and Tryon, 2004;Faurholt-Jepsen et al, 2012;Foster et al, 1978;Glod et al 1992;Godfrey and Knight, 1984;Haynes et al, 2006;Joffe et al, 2009;Korszun et al, 2002;Raoux, 1994;Royant-Parola et al, 1986;Teicher et al, 1997;Todder et al, 2006;Todder et al, 2007;Volkers et al, 2002;Volkers et al, 2003;Winkler et al, …”
Section: Search Resultsmentioning
confidence: 99%
“…1 study validated the RT3 accelerometer Sharpe et al, 2006a. 16 studies used as part or in full an OBM to capture physical activity Berle, Hauge, Oedegaard, Holsten, & Fasmer, 2010;Farrow, Hunter, Wilikinson, Green, & Spence, 2005;Gothelf et al, 2002;Hauge, Berle, Oedegaard, Holsten, & Fasmer, 2011;Janney et al, 2008;Jerome et al, 2009;McCormick et al, 2009;McCormick et al, 2008;McKibbin et al, 2006;Scheewe, 2008;Scheewe et al, 2011;Sharpe et al, 2006a;Wichniak et al, 2011;Yamamoto et al, 2011. 19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012.…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…32 Other actigraphy studies have observed lowered activity levels in patients with depression or schizophrenia compared with healthy controls, with more pronounced differences in those with schizophrenia and particularly those taking antipsychotic medication. 13,[33][34][35] Bipolar disorder has also been associated with higher variability in activity patterns and a phase advanced peak of the activity-rest cycle. 34,35 However, no study has yet investigated multiday sleep-wake and activity profiles across more than 2 diagnostic groups.…”
Section: Introductionmentioning
confidence: 99%